Optimalisasi Penggunaan Multimedia Sebagai Sumber dan Bahan Pembelajaran Pendidikan Agama Islam (PAI) - Muharrani, Muharrani; Murhayati, Sri; Zaitun (LPPM Institut Agama Islam Diniyyah Pekanbaru, 2025)
Abstract Efforts to face the challenges of the digital era, where students as 'digital natives' need a more interactive and interesting learning approach. For this reason, it is necessary to optimize the use of multimedia in learning, especially PAI. This research aims to explore optimizing the use of multimedia as a source and learning material for Islamic Religious Education (PAI). The method used is qualitative research with a library approach, by reviewing literature related to the use of multimedia in PAI learning, through documentation and content analysis from literary sources such as books, notes and research reports from previous researchers. The research results show that the integration of multimedia in PAI learning can increase student engagement, as well as facilitate more effective learning through simultaneous processing of visual and auditory information. In conclusion, optimizing the use of multimedia in Islamic religious education is needed to make the material more relevant and interesting for the current generation, while increasing the effectiveness of learning in the context of modern education. The contribution of this research can increase student involvement, enrich learning methods, and strengthen understanding of Islamic Religious Education material through the use of innovative multimedia. Keywords: Multimedia; Resources and Materials; Student Engagement; Islamic Religious Education (PAI) Abstrak Upaya menghadapi tantangan era digital, di mana siswa sebagai 'digital natives' membutuhkan pendekatan pembelajaran yang lebih interaktif dan menarik. Untuk itu diperlukan optimalisasi penggunaan multimedia dalam pembelajaran khusunya PAI. Penelitian ini bertujuan untuk mengeksplorasi optimalisasi penggunaan multimedia sebagai sumber dan bahan pembelajaran Pendidikan Agama Islam (PAI). Metode yang digunakan adalah penelitian kualitaif dengan pendekatan kepustakaan, dengan mengkaji literatur terkait penggunaan multimedia dalam pembelajaran PAI, melalui dokumentasi dan analisis isi dari sumber-sumber literatur seperti buku, catatan, dan laporan riset dari peneliti sebelumnya. Hasil penelitian menunjukkan bahwa integrasi multimedia dalam pembelajaran PAI dapat meningkatkan keterlibatan siswa, serta memfasilitasi pembelajaran yang lebih efektif melalui pengolahan informasi visual dan auditori yang simultan. Kesimpulannya, optimalisasi penggunaan multimedia dalam pendidikan agama Islam diperlukan untuk membuat materi lebih relevan dan menarik bagi generasi saat ini, sekaligus meningkatkan efektivitas pembelajaran dalam konteks pendidikan modern. Adapun kontribusi dari penelitian ini dapat meningkatkan keterlibatan siswa, memperkaya metode pembelajaran, dan memperkuat pemahaman materi Pendidikan Agama Islam melalui penggunaan multimedia yang inovatif. Kata kunci: Multimedia; Sumber dan Bahan; Keterlibatan Siswa; PAI.